2013
DOI: 10.1098/rspb.2012.2526
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for directional evolution of body mass in herbivorous theropod dinosaurs

Abstract: The correlation between large body size and digestive efficiency has been hypothesized to have driven trends of increasing mass in herbivorous clades by means of directional selection. Yet, to date, few studies have investigated this relationship from a phylogenetic perspective, and none, to our knowledge, with regard to trophic shifts. Here, we reconstruct body mass in the three major subclades of non-avian theropod dinosaurs whose ecomorphology is correlated with extrinsic evidence of at least facultative he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 60 publications
3
54
0
2
Order By: Relevance
“…Although a previous study found little evidence for directional trends of body size increase in herbivorous maniraptoran clades [69], this does not conflict with our observation that some body size shifts in maniraptorans (and other coelurosaurs) coincide with the appearance of craniodental, or other, evidence for herbivory (Table 3; e.g., [67],[68],[70]). …”
Section: Discussionsupporting
confidence: 53%
“…Although a previous study found little evidence for directional trends of body size increase in herbivorous maniraptoran clades [69], this does not conflict with our observation that some body size shifts in maniraptorans (and other coelurosaurs) coincide with the appearance of craniodental, or other, evidence for herbivory (Table 3; e.g., [67],[68],[70]). …”
Section: Discussionsupporting
confidence: 53%
“…Shifting the focus from a putative link with digestive physiology that might, in many cases, rest on a rhetoric misunderstanding, to an ecological approach, might finally yield better theories about the relationship of diet and body size that match actually observed patterns both in extant herbivores and in the fossil record (e.g. [132]). …”
Section: Outlook On Outliers: Which Rule Do Exceptions Prove?mentioning
confidence: 99%
“…These values were used to place large-bodied theropod species into generalized mass bins and identify time spans where apex predators achieved relative gigantism (43,500 kg). We recognize that mass extrapolation adds additional uncertainty to size estimates over FL alone, specifically among clades with variable bauplans 58 . However, we do not use mass estimates as point values here and binning protocol minimizes point value error.…”
Section: Methodsmentioning
confidence: 99%